Creativity for innovation management - Goller, Ina; Bessant, J. R. (London Routledge, 2017)
Creativity for Innovation Management is a rigorous yet applied guide which illustrates what creativity is, why it matters, and how it can be developed at both individual and group levels. Unlike many technique-oriented books, this book will combine theory and practice, drawing on the latest research in psychology, organizational behaviour, innovation and entrepreneurship. This exciting new text outlines the necessary skills and competences for innovative and creative processes. It provides opportunities to explore these and also to develop them via a wide variety of activities linked to relevant tools and techniques, as well as a range of case studies. By working through key competence areas at personal and then team levels, students then have an opportunity to practice and enhance these skills. This will be complemented by online resources which will provide students with access to key tools and techniques plus activities to help develop their creativity. This textbook is ideal for students of innovation, management and entrepreneurship, as well as professionals in those industries that want to excel by developing and applying their own creativity at work.--Provided by publisher.
Keywords: Creative ability in business; Management -- Technological innovations